青年學子網路資訊尋求行為及其輔導策略之研究 Research on the Young Adults' Online Information Seeking Behavior - Chaoyun Liang; Wei-Ju Chen (Jiàoyù zīliào yǔ túshūguǎn xué, 2003)
對於涉世未深的青年學子而言，網路科技帶來的不只是豐富多元的資訊交流，更是同濟間競相追尋在真實世界無法企求的感官刺激，同時也將形成個人或群體顛覆行為的養成溫床。本研究即藉由對青年學子的上網動機與資訊尋求行為的了解，對政府相關機構提出具體可行的輔導策略，並從學校與業者兩個方向配合實施。專家座談與問卷調查是本研究主要使用的兩種工具。 The aim of this research is twofold: first, to explore the young adults online information seeking behavior; second, to provide feasible coaching approaches for the government. On the basis of these analyses, this research will provide the policy guides from diverse perspectives including government, school, and business settings. Expert discussion and questionnaire investigation are the major methods used in this research project.